HOLISTICS JOURNAL HOLISTICS JOURNAL HOSPITALITY AND LINGUISTICS: The Implementation of Visualization, Auditory, Kinesthetic (Vak) Model in Teaching Speaking - Sri Wahyu (HOLISTICS, 2021)
The title of this article is the implementation of Visualization, Auditory, Kinesthetic (VAK) model in teaching speaking to the eighth grade students of junior high school 16 Palembang. The problem of this study is to find out whether it was effective or not to implement the Visualization, Auditory, Kinesthetic (VAK) model in teaching speaking to the eighth grade students of junior high school 16 Palembang. This study used one group pretest-posttest design, a single group was measured or observed not only after being exposed to a treatment of some sort, but also before. Based on the analysis of the data, it was found out that the students’ average score in pretest was 62.85. the highest score 69 which was achieved by one student, while the lowest score was 63 which was achieved by two students. The students’ average score in posttest was 67.44. The highest score was 71.5 achieved by three students. While the lower score was 60.5 achieved by one student. From the result of the matched t-test, the obtained value was higher than t-critical value. The result of matched t-test formula was 8.5 and t-critical value of t-distribution table was 1.679. It means that the use of “VAK model” was effective significantly in teaching speaking to the eighth grade students of Junior High School 16 of Palembang.